WEB-BASED PUBLIC METEOROLOGICAL INFORMATION DATA REQUEST APPLICATION DESIGN AT METEOROLOGICAL STATIONS - Eni Pudjiarti; Siti Faizah (Sean Institute, 2022)
In order to provide reliable and reliable meteorological data and information, Budiarto Meteorological Station has problems how to simplify the flow of the request process and the provision of meteorological information data, especially for public meteorological information.In addition, many users still do not understand what public meteorological information data can be provided by the Meteorological Station as well as the imposition of tariffs applicable to each meteorological information in accordance with Government Regulation No. 47 of 2018 on Types and Tariffs on Types of Non-Tax State Revenues Applicable to the Meteorological, Climatology and Geophysical Agencies.The current process flow is considered too long, so the process of requesting and providing public meteorological information data takes a long time.Development of public meteorological information data request application using web-based application design using waterfall method.The language used to design web-based applications using PHP, HTML and CSS programming languages and databases is MySQL.The use of this web-based application can make it easier for users to request public meteorological data, so that public meteorological data can be obtained immediately without having to wait a long time.